The Effect of Financial Education in The Family, Financial Literature, and Self-Control on Financial Management through Consumption Rationality - Rohim, Ahmad Miftahur; Haryono, Agung; Wardoyo, Cipto (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2022)
The purpose of this research is to analyze the influence of family financial socialization, financial literacy, self-control, and rationality of consumption on money management of Bachelor students of faculty Economics Universitas Negeri Malang Class of 2017. This research conducts in quantitative which has an explanation method. The data collection uses a questionnaire for 291 students as the samples. The data analysis uses Path analysis of SPSS program version 26. The results of the analysis test in this study indicate that family financial socialization, financial literacy, self-control, and rationality of consumption affect the money management of Bachelor Students of Faculty Economics Universitas Negeri Malang Class of 2017.